Green Accounting and Governance for Advancing Sustainable Village Development - Rizka, Dio; Rahmawati (Inovasi Analisis Data, 2025)
Objective: This paper seeks to gain an understanding of the integration of institutional capacity, collective awareness, regulatory behavior, conservation accounting activities and participatory participation on sustainable development in public sector governance systems. Methods: Quantitative structural modeling was used to investigate interrelations between governance constructs with careful tests of measure validity, structural paths, and indirect effects. The analytical approach has strong robustness and reliability, with extensive methodological examination, discrimination measures, and iterative model validation. Results: Participatory engagement is the most important factor for the predictions of sustainability results, illuminating its fate, strengthening responsiveness, shared ownership, and social legitimacy. Institutional capacity demonstrates high direct and indirect contributions, illustrating that managerial consistency, administrative competence, and integrated actions are the conditional base for sustainable development. AS only affects SD through active participation in the former and internal decision transparency for EA. Regulating behaviour supports sustainability primarily by its capacity to entrench the dynamics of engagement. Novelty: The paper develops a governance-participation integrative model, which represents an alternative to traditional compliance- and accounting-based explanations. It shows that sustainable development is driven more by institutional capacity and social embeddedness than technical systems per se, generating a new theoretical way of thinking for public sector sustainability research. Research Implications: Implications favour reforms that strengthen institutional capacity, broaden participation venues, and integrate environmental accounting into strategic governance processes. The theoretical framework presented here promotes a prospective approach to developing ‘inclusive and resilient’ sustainability policies.